Direct and Efficient Synthesis of Pyrrole-3-carbaldehydes by Vilsmeier–Haack Formylation of Pyrroles with Sterically Crowded Amides - Ilyin, Petr V.; Pankova, Alena S.; Kuznetsov, Mikhail A. (Synthesis, 2012)
A simple and convenient synthetic method to prepare N-substituted pyrrole-3-carbaldehydes by Vilsmeier–Haack formylation of pyrroles using sterically crowded formamides was developed. The dependence of the formylation regioselectivity on steric features of substrates and reagents is discussed.
Keywords: formylation; pyrroles; aldehydes; electrophilic aromatic substitution; formamides; Vilsmeier–Haack